The Influence of Preoperative Tibial Bone Marrow Edema on Outcomes After Medial Opening-Wedge High Tibial Osteotomy. (2nd December 2020) - Yang, Hong-Yeol; Kang, Sung-Ju; Kwak, Woo-Kyoung; Song, Eun-Kyoo; Seon, Jong-Keun
Abstract : Background: The relationship between preoperative subchondral bone marrow edema (BME) in the osteoarthritic knee and pain has been established. However, little is known about the influence of preoperative BME on outcomes after medial opening-wedge high tibial osteotomy (MOHTO). The purpose of this study was to clarify the association between preoperative BME severity and clinical outcomes after MOHTO at intermediate follow-up. Methods: We reviewed the cases of 105 consecutive patients who underwent MOHTO for osteoarthritis of the knee with preoperative subchondral BME in the medial aspect of the tibia between January 2005 and December 2015. BME was evaluated using magnetic resonance imaging (MRI). The sizes of the BME lesions were determined on the basis of the maximum diameter and were classified as small (<1 cm), medium (<2 cm), large (<4 cm), or very large (diffuse; >4 cm). Associations between preoperative BME severity and postoperative outcomes at a mean follow-up of 6.2 years (range, 2.0 to 14.3 years) were evaluated according to a Spearman correlation matrix with each reviewer's grades. Functional outcomes were assessed using the Hospital for Special Surgery (HSS) score, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Knee Society Score (KSS), and Short Form-12 (SF-12) questionnaire. Survival rate and complications were also evaluated. Results: The degree of preoperative BME was not significantly correlated with postoperative outcomes (p > 0.05). There were significant improvements between the preoperative and latest follow-up assessments in all functional outcome categories (p < 0.001). Patients demonstrated marked improvements with respect to pain, function, and quality of life. The overall survival rate was 95.2%, with a mean follow-up of 6.2 years. Six major complications were identified in 5.7% of the patients, and these resulted in 5 patients (4.8%) who had conversion to total knee arthroplasty. Conclusions: We did not find any correlation between preoperative subchondral BME severity and postoperative outcomes. MOHTO showed good functional outcomes, a low major complication rate, and an excellent survival rate with a mean follow-up of 6.2 years, regardless of the degree of preoperative BME. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.